Roles of Existing Policies on The Conservation and Management of Cultural Heritage in Kathmandu Valley, Nepal - Subedi, Salik Ram; Shrestha, Sudha (Journal of Advanced College of Engineering and Management, 2023)
In 1956, the Ancient Monuments Preservation Act (AMPA) was first introduced, ushering in a more contemporary approach to cultural preservation in Nepal. The focus of this legislation is primarily on the material (physical) aspects of cultural heritage. The Guthi Corporation, formed by the Government of Nepal under the Guthi Corporation statute of 1976, focuses on the intangible legacy of the Kathmandu valley in a manner similar to that described above. The Department of Archaeology (DOA), a federal government body backed by the AMPA and in charge of safeguarding the country's cultural heritage. International organizations like the United Nations Educational, Scientific and Cultural Organization (UNESCO) criticized the difficulties in managing the Kathmandu valley's world heritage sites, which led to their inclusion on the endangered list in 2003, which has since been removed. The purpose of this research paper is to examine the effects that different government organizations' (stakeholders') policies have throughout time on the management and preservation of the cultural heritage of the Kathmandu valley. In order to maintain cultural assets using historical as well as case study methodologies, the research of this article recommends a review of current policies on dispersed policies and organizational responsibilities. Study reveals that now the time to development of unified policies and organisation to minimise the overlapping roles for good management and conservation in the Kathmandu valley, which will primarily be based on local cultural context as well as UNESCO criteria.